Analisis Sentimen Objek Wisata Danau Toba berdasarkan Ulasan Pengunjung menggunakan Algoritma Support Vector Machine - Immanuel Tri Putra Sihaloho; Dian Eka Ratnawati; Bayu Rahayudi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Lake Toba is one of the tourist destinations in Indonesia and is designated as one of the five developments of the National Tourism Strategic Area which is the government's super priority program in tourism development in Indonesia. Therefore, Lake Toba tourism managers need to know the perspective of visitors as evaluation material. Data acquisition of visitor reviews of Lake Toba attractions can be easily obtained through the Tripadvisor website using web scraping techniques. Reviews from Tripadvisor will be categorized into three classes, namely positive, neutral and negative. Before doing the classification, do text preprocessing to process the data into more structured data for research needs and carry out word weighting using the Term Frequency - Inverse Document method. Then the classification is carried out using the Support vector Machine algorithm. The best results in testing using the Support vector Machine algorithm are testing on 2 sentiment classes with a total of 220 data, using a linear kernel and a C value of 100. Accuracy, precision, recall, and f1-score values ​​in this machine learning model are successively were 83%, 84%, 83%, and 83%.